2015
DOI: 10.1096/fasebj.29.1_supplement.969.27
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of WNK4 on the Na+:ClCotransporter is modulated by Intracellular Chloride

Abstract: IntroductionThe effect of WNK4 on the renal Na+:Cl‐ cotransporter, NCC is controversial since several studies in vitro and in vivo have shown negative or positive effects. We hypothesize that both effects coexist and are modulated by the intracellular chloride concentration ([Cl‐]i). Piala et al. (2014) showed that L‐WNK1 is a Cl‐‐sensitive kinase and identified two leucine residues forming the Cl‐‐binding site. These leucines are conserved in WNK isoforms.Materials and MethodsWe used the functional expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Specifically, WNKs’ homo- or heterodimer formation induces the conformational change of WNK kinase, which in turn facilitates autophosphorylation at the T-loop activation kinase domain, leading to WNK activation [ 28 ]. Thus, mutations at the T-loop activation kinase domain, such as D321A or D321K-K186D, ablate WNK kinase activity [ 32 ]. In addition, mutations of catalytic homologous serine, including S335A of WNK4 and S382A of WNK1, eliminate their phosphorylation activity.…”
Section: Familial Hypertension Stemming From Genetic Defects In Wnk S...mentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, WNKs’ homo- or heterodimer formation induces the conformational change of WNK kinase, which in turn facilitates autophosphorylation at the T-loop activation kinase domain, leading to WNK activation [ 28 ]. Thus, mutations at the T-loop activation kinase domain, such as D321A or D321K-K186D, ablate WNK kinase activity [ 32 ]. In addition, mutations of catalytic homologous serine, including S335A of WNK4 and S382A of WNK1, eliminate their phosphorylation activity.…”
Section: Familial Hypertension Stemming From Genetic Defects In Wnk S...mentioning
confidence: 99%
“…In addition, it was reported that chloride ions bound to the chloride-binding pocket located in the kinase domain inhibited the autophosphorylation and activation of WNK [ 95 ]. Studies indicated that WNK4 L322F mutation in the chloride pocket desensitizes WNK4′s binding affinity to Cl − ions, therefore resulting in the increased autophosphorylation of WNK4, even in the presence of a higher chloride concentration [ 32 ]. WNK1, WNK3, and WNK4 each express distinct chloride-binding affinities, in which chloride binds most efficiently to WNK4 and least efficiently to WNK3 [ 27 , 95 ].…”
Section: Familial Hypertension Stemming From Genetic Defects In Wnk S...mentioning
confidence: 99%
See 1 more Smart Citation
“…4 The intracellular chloride concentration ([Cl − ] i ) regulates the autophosphorylation of WNK4. 5 The binding of Hypertension. 2021;78:1039-1041.…”
Section: See Related Article Pp 1027-1038mentioning
confidence: 99%
“…Recently it was also demonstrated using a transgenic mouse model expressing a Cl − sensor that raising extracellular K + transiently increases the intracellular Cl − concentration in the DCT, and that blockade of Kir4.1/Kir5.1 or inhibition of the Cl − channel ClC-K2 increases intracellular Cl − concentrations (33). Hence, diet induced changes in the extracellular K + concentration are thought to alter the basolateral plasma membrane potential via Kir4.1/Kir5.1, resulting in altered intracellular Cl − levels and ultimately modulation of the Cl − sensitive lysine deficient protein kinase (WNK) 1 and 4, affecting the WNK-SPAK/OSR1 kinase signaling pathway and NCC activity (3,28). Considering this, the high K + induced increase in Kir4.1 and Kir5.1 expression in the DCT is surprising.…”
mentioning
confidence: 99%